Influence of Postoperative Patient-Controlled Analgesia on Hemorheology in Patients Undergoing Hip Arthroplasty - Bai, Yiping; Mo, Liqun; Luan, Liming; Zhang, Daiying (Zeitschrift für Orthopädie und Unfallchirurgie, 2020)
Objective To test the hypothesis that patient-controlled analgesia (PCA) contributes to improvement of hemorheology in patients undergoing hip arthroplasty.Methods 120 patients, aged 60 – 75 years old, undergoing hip arthroplasty under spinal anesthesia, were randomly divided into group PCA (n = 60) and control group (n = 60). Patients in PCA group received PCA in postoperative 3 days. Blood samples from the median cubital vein were collected at five time points: before anesthesia (T1), after surgery (T2), 6 h after surgery (T3), 24 h after surgery (T4), 48 h after surgery (T5). Hemorheological parameters were measured, including whole blood viscosity at a high shear rate (Hηb), whole blood viscosity at a low shear rate (Lηb), reduced viscosity (ηr), plasma viscosity (ηp), hematocrit (Hct), erythrocyte aggregation index(EAI) and erythrocyte deformation index (EDI). Noninvasive blood pressure and heart rate at T1-5 and pain scoring of visual analogue scale (VAS) score at T2-5 were recorded.Results (1) Compared with T1, Hηb, Lηb, ηp, ηr decreased significantly at T3–5 with EAI decreased significantly at T5 in group PCA (p < 0.05), EDI increased significantly at T5 in group C (p < 0.05). (2) Compared with group C, Hηb, Lηb, ηp, ηr, EAI decreased significantly at T5 with Lηb concurrently decreased at T4 in group PCA (p < 0.05).Conclusion Postoperative pain may increase blood viscosity in patients undergoing hip arthroplasty, mainly via plasma viscosity, erythrocyte aggregation and rigidity, and which could be improved by postoperative PCA.
Keywords: hemorheology; patient-controlled; analgesia; hip arthroplasty